2002
DOI: 10.1021/ma0118421
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study on the Rate Retardation in Radical Polymerization of Styrene with Addition−Fragmentation Chain Transfer

Abstract: The polymerization of styrene mediated by a polystyryl dithiobenzoate was studied by electron spin resonance spectroscopy to determine the concentration of the intermediate radical produced by the addition of polystyryl radical to the dithiobenzoate. The polymerization was also followed by dilatometry to estimate the concentration of the growing radical. The results showed that the fragmentation of the intermediate radical is a fast process with a relevant rate constant on the order of 10 4 s -1 (at 60 °C) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
432
2
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(476 citation statements)
references
References 21 publications
37
432
2
3
Order By: Relevance
“…[44] Retardation has also been observed in polymerizations of styrene and methacrylates, and is pronounced when high concentrations of dithiobenzoate RAFT agents [137] are used. [9,[52][53][54][55]133,137,140,141] With lower concentrations of RAFT agents such as cyanoisopropyl dithiobenzoate 8 and cumyl dithiobenzoate 22 (<0.03 M), we have shown that rates of polymerization for styrene and MMA are little different from that expected in the absence of RAFT agent and appear independent of the particular dithiobenzoate. [9,44,52] Inconsistencies in reported rates of polymerization suggest that, in some cases, lower rates may in part be attributed to extraneous factors such as impurities in the RAFT agent or incomplete degassing.…”
Section: Side Reactions In Raftmentioning
confidence: 67%
See 1 more Smart Citation
“…[44] Retardation has also been observed in polymerizations of styrene and methacrylates, and is pronounced when high concentrations of dithiobenzoate RAFT agents [137] are used. [9,[52][53][54][55]133,137,140,141] With lower concentrations of RAFT agents such as cyanoisopropyl dithiobenzoate 8 and cumyl dithiobenzoate 22 (<0.03 M), we have shown that rates of polymerization for styrene and MMA are little different from that expected in the absence of RAFT agent and appear independent of the particular dithiobenzoate. [9,44,52] Inconsistencies in reported rates of polymerization suggest that, in some cases, lower rates may in part be attributed to extraneous factors such as impurities in the RAFT agent or incomplete degassing.…”
Section: Side Reactions In Raftmentioning
confidence: 67%
“…The intermediates have been observed directly by EPR in RAFT polymerizations of styrene and acrylate esters and in model reactions with dithiobenzoate and dithiophosphonate RAFT agents. [112,[131][132][133][134][135][136] The intermediates 3 or 5 are not detectable during MMA polymerizations or in polymerizations with aliphatic dithioester, trithiocarbonate, xanthate, or dithiocarbamate RAFT agents. This is attributed to the greater rate of fragmentation and the correspondingly shorter lifetime of the adduct in these polymerizations.…”
Section: Evidence In Support Of the Raft Mechanismmentioning
confidence: 99%
“…This reaction has to be relatively fast to effectively compete with the propagation and termination reaction (k β = 4·10 6 L·mol -1 ·s -1 [8]) with k β approaching conventional diffusion-controlled termination reactions. Inspection of Scheme 1 demonstrates that the main equilibrium of the RAFT mechanism involves the reaction of two macromolecular species: the macroRAFT agent (3) and the growing macroradical.…”
Section: Chain Length Distributionsmentioning
confidence: 99%
“…Evidence has been collated to underpin both theories, e.g., via electron spin resonance spectroscopy [8,9], computer-based modelling strategies [10][11][12], the observation of intermediate species and their possible termination products [13][14][15], or through high-level ab initio molecular orbital calculations [16], with the experimental outcomes apparently supporting either mechanism. In an attempt to harmonize the apparent contradictory experimental results gathered by the scientific community, a reversible intermediate termination reaction was hypothesized [17] (see Scheme 2), which basically says that the intermediate RAFT radical 4 in Scheme 1 is resonancestabilized if Z is phenyl or naphthyl with the radical site being delocalized over the aromatic system.…”
Section: Introductionmentioning
confidence: 99%
“…The only caveat is that side reactions must be absent. [31][32][33] Such side reactions include intermediate radical termination (IRT), [34][35][36] slow fragmentation (SF), 37,38 or impurities in the RAFT agent. 31,32 By combining RAFT with a simple nonsteady-state method, the effects of i and x on k t can be accurately and reliably evaluated, avoiding the problem of broad MWDs.…”
Section: Introductionmentioning
confidence: 99%